Validation of PhET-Based Core Physics Teaching Materials to Improve Activities and Learning Outcomes of Physics Education Students - Susilawati Susilawati; Aris Doyan; Joni Rokhmat; Gunawan Gunawan; I Wayan Gunada; Hikmawati Hikmawati (Postgraduate, University of Mataram, 2023)
The development of PhET-based core physics introductory teaching materials to increase the activities and learning outcomes of physics education students has been successfully carried out. The purpose of this development is to produce teaching materials for introductory PhET-based core physics courses that are feasible to increase the activity and learning outcomes of physics education students. The device development uses a 4D model (define, design, develop, and disseminate). The tools developed are in the form of Semester Program Plans, Student Activity Sheets, core physics teaching materials, student activity instruments and student learning outcomes instruments. The results showed that the PhET-based core physics teaching materials were very valid. This means that the teaching materials for introductory core physics courses based on the use of PhET are very feasible to use in increasing the activities and learning outcomes of physics education students.